Analisa Identifikasi Core Point Sidik Jari - Arifah P, Diah; Rudiaman S, Daniel (Prosiding SNATIKA, 2017)
The fingerprint recognition system is one of the biometric technologies that can be used in identifying a person. The fingerprint has a midpoint called the core point. Core Point has a very important role because it will serve as one of the parameters in the process of identification and classification of fingerprints at the stage of feature extraction process. Core Point is also one of the important parameters in determining the fingerprint formula. In this research, a technique will be developed to determine the midpoint automatically using the poincare index algorithm. The first stage is the pre-processing of the fingerprint image which includes (1) the grayscaling process (converting the color image to black and white image); (2) normalization process (improving image quality when image is too dark or too bright); (3) binary process (the threshold used is 80% of the average). The second stage is to identify the location of core points through several stages: (1) making block orientation; (2) smooth orientation process; (3) determination of core point using poincare index algorithm. The output of this research will be the obtained core point (midpoint) of the fingerprint which will be used for further fingerprint identification